Design and Build Online Store Website at Toko Mas Djanoko - JImmy Wiyanto; Albertus Dwiyoga Widiantoro; Agus Cahyo Nugroho (Journal of Business and Technology, 2022)
Sources of information and media for communication are incredibly simple for us to obtain and use in the development of technology in the era of digital transformation as it is today. The internet is one example of how quickly information and communication technology has advanced. There is little doubt that this has a significant impact on many areas, including the business sector. Businesses can expand quickly in their ability to perform trading activities thanks to technology improvements. Even though technology has evolved and changed, many firms are still unable to keep up with new developments. Toko Mas Djanoko is one illustration. This jewelry store continues to sell its goods using traditional strategies. Toko Mas Djanoko is undoubtedly not benefiting from this too much. By developing a store website that is connected to the marketplace, this study aims to offer Toko Mas Djanoko a solution for marketing and introducing their items. It is intended that this website would make Toko Mas Djanoko more successful at selling their goods. adopting the System Development Life Cycle (SDLC) approach to system development. The study's findings show that Toko Mas Djanoko's items may be successfully and widely marketed thanks to the website system that was developed.